Food consumption and nutritional effects of consumer-oriented food subsidies - Kumar, Shubh K.; Alderman, Harold (International Food Policy Research Institute, 1988)
An examination of the experience of the various countries operating food subsidies reveals great diversity in the objectives, instruments, and effects of these programs. However, three broad observations can be made that are relevant to the analysis of their nutritional consequences. First, although improved nutrition is seldom an explicit objective, promoting food security for those segments of the population perceived to be vulnerable is a rationale in the majority of the cases examined.1 Second, this rationale is translated in many cases into a combination of interventions in agricultural pricing and procurement alongside a distribution mechanism that protects consumers of these commodities through subsidized prices. Third, although food security may be the overriding concern in the majority of consumer food subsidy programs, the choice of commodities often includes nonbasic food items, such as sugar, and nonfood items, such as kerosene, tea, salt, and soap, which have also been considered essential commodities and therefore were included in the subsidy.